Cutting a chemical bond with demon's scissors: Mode- and bond-selective reactivity of methane on metal surfaces - Lozano, Ariel (2015)
In this paper we discuss several aspects of methane reactive sticking on Pt(111) in the light of supersonic molecular beam experiments (including state-resolved measurements) and quasi-classical trajectory calculations based on an accurate reaction specific reactive force field constructed from Density Functional Theory (DFT) data. With the aim of understanding the origin of the full bond selectivity recently achieved experimentally and to predict how selectivity depends on the collision conditions, we discuss in detail, the role of initial translational and (mode-specific) vibrational energy of CH4 and all its deuterated isotopomers, as well as surface temperature effects. Last but not least, the systematic and detailed theoretical analysis presented here serves as an illustration of the possibilities and usefulness of accurate reaction specific reactive force fields built from DFT data. This approach allows investigating dynamical aspects of the interaction of polyatomic molecules on surfaces through quasi-classical trajectory calculations accounting for the full dimensionality of the system (including both molecular and surface degrees of freedom): something that a few years ago was just a dream for the gas-surface dynamics community.